Effects of mental imagery styles on shoulder and hip rotations during preparation of pirouettes - Golomer, E.; Bouillette, A.; Mertz, C.; Keller, J. (Journal of Motor Behavior, 2008)
To analyze individual behavior in spatial navigation especially for pirouette preparations (complete whole-body rotations), the authors studied horizontal shoulder-hip interactions under 2 constraints: postural (right and left supporting legs [SL]) and spatial (clockwise [CW] and counterclockwise [CCW]). They performed kinematic analysis at the start and end of the shoulder-hip horizontal rotations (run-up) with regard to imagery of motor actions. On the basis of the Vividness of Movement Imagery Questionnaire, they classified 8 female expert ballet dancers and 7 untrained female participants according to their movement imagery style (kinesthetic and visual). At the run-up's end, the shoulders initiated the turn independently of SL but differently depending on training: CW for dancers and CCW for untrained participants (their commonly used direction). Kinesthetic and mixed imagery styles prevailed in dancers, whereas simply a mixed style appeared among untrained participants. Thus, dance training enhances the imagery of kinesthetic sensation and influences the choice of spatial direction, facilitating the body-space interaction.